Autism Spectrum Disorders in Adults - Barahona Corrêa, Bernardo; van der Gaag, Rutger-Jan (Springer International Publishing : Imprint: Springer, 2017)
In this book a group of international experts guide the reader through the clinical features of adults with autism spectrum disorders, describe the care needs of patients and their families, explain the evolution of the disorders into old age, and highlight what can be done to help. Detailed attention is paid to the medical and psychiatric problems of adults with these disorders and the approach to their education and professional integration. In addition, expert neuroscientists summarize current views on the neurobiology of autism. Autism spectrum disorders are devastating neurodevelopmental disorders. Although diagnosis and therapeutic interventions usually take place in infancy, they are chronic lifelong conditions. Surprisingly, the literature on autism spectrum disorders in adults is scarce. Moreover, most mental health professionals working with adults have little training in autism, and adult mental health services around the world are rarely prepared to address the needs of these patients, which tend to increase with age. This book therefore fills a crucial gap in the literature and will prove useful for all who care for and deal with adults in the Autistic Spectrum.
Keywords: Medicine.; Psychiatry.; Social work.; Developmental psychology.; elektronické knihy; electronic books